Pemanfaatan Youtube Sebagai Media Pembelajaran Guna Meningkatkan Motivasi Belajar Peserta Didik - Milala, Dita; Walujan, Melisa; Pangalila, Theodorus (Tumoutou Social Science Journal, 2024)
This research investigates the extent to which YouTube, as a learning medium, enhances students' comprehension and motivation to learn. The aim of this study is to evaluate the application of YouTube technology at SMP Negeri 2 Tondano. The research employs qualitative methods, utilizing observation and interview techniques for data collection. YouTube is primarily known as a platform for sharing and uploading videos, but it also serves educational purposes, providing insights and facilitating learning. The use of YouTube as a learning medium has garnered a positive response from students, as evidenced by the study's findings. The implementation of YouTube-based learning at SMP Negeri 2 Tondano has demonstrated a positive impact, with students showing increased enthusiasm and motivation. When engaged in learning through YouTube, students are more active and engaged. Thus, YouTube serves as an effective learning medium to boost students' motivation and participation in the learning process.